Crystal structures of three salts of the triphenylsulfonium ion - Rylan Artis; Waylan Callaway; Elizabeth Heyward; Naomi Reyes; Gavin Roberts; Kaitlyn Van Ostenbridge; Clifford W. Padgett; Will E. Lynch (Acta Crystallographica Section E: Crystallographic Communications)
The reactions of triphenylsulfonium chloride ([TPS][Cl]) with various acids in methanol yield the corresponding salts triphenylsulfonium triiodide, C18H15S+·I3− or [TPS][I3] (I), triphenylsulfonium perchlorate, C18H15S+·ClO4− or [TPS][ClO4] (II), and triphenylsulfonium hexafluorophosphate, C18H15S+·PF6− or [TPS][PF6] (III), as crystalline products. These crystals were structurally characterized by single-crystal X-ray diffraction. In all three compounds, the sulfur atom in the triphenylsulfonium cation adopts a distorted trigonal–pyramidal geometry. [TPS][I3] (I) and [TPS][PF6] (III) both crystallize in the space group P21/n, while [TPS][ClO4] (II) crystallizes in P21. The S—C bond lengths are comparable across the three salts, and the S—C—S bond angles are consistently between 102 and 106°. Hirshfeld surface analyses reveal that each structure is dominated by hydrogen-based intermolecular contacts, supplemented by anion-specific interactions such as I...H in (I), O...H in (II), and F...H in (III). These contacts organize the ions into mono-periodic ribbon- or chain-like arrangements. No significant π–π stacking is observed.